SCARF JOINTS IN GLUED LAMINATED TIMBER OF PARICÁ - Terezo, Rodrigo Figueiredo; Rosa, Talitha Oliveira; Furtado, Francisco Raphael Cabral; Ampessan, Camilla Gabriela Melo; Cunha, Alexsandro Bayestorff; do Valle, Angela (Floresta, 2021)
Glued Laminated Timber (GLULAM) is manufactured by joining wood lamellae glued in parallel to each other. GLULAM with larger longitudinal dimensions can be obtained by gluing the tops of two wood lamellae. The gluing of the tops can be done using wedge-shaped scarf joints. However, the joints produce a discontinuity in the wood, being areas considered as susceptible to rupture. In this way, the objectives were to evaluate four slopes (1:6; 1:8; 1:10 and 1:12) in scarf joints of Schizolobium parahyba var. amazonicum timber for use with structural purposes; and glued laminated timber beams – GLULAM manufactured with the scarf joint with the best performance by the modulus of elasticity – MOE (theoretical and analytical MOE values). Each laminated timber used to produce the test specimens was classified by visual inspection that aimed at the absence of defects, such as knots. The test specimens were adapted to the four-point static bending test and to the tensile strength test in parallel to the grain direction, in accordance to the NBR 7190 (1997). The slope of 1:12 showed the best results, while the slope of 1:6 presented the lowest results when compared with the control. The beams of 5 x 9.5 x 220 cm, composed of joints with slopes of 1:12, showed MOE values statistically equal to those of beams without joints. The scarf joint proved to be an alternative for use in glulam beams of paricá, as it presents stiffness and strength comparable with those of beams without a joint.